PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA (STUDI KASUS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020-2023) - Anton Sugiarto; Friyani, Rita (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study was to examine the effect of financial ratios on earnings growth. The population of this study is Banking Companies listen on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The sampling technique used in this study is purposive sampling technique, which is a sample determination technique by selecting samples according to certain criteria. This study used 20 companies as samples, with an observation time of four years so that there were 80 obsevation data. This study uses secondary data sourced from the company’s annual report. In this study the data analysis technique uses multiple linier regression analysis. The results of hypothesis testing show that simultaneously Current Ratio, Cash Ratio, Return On Assets, Net Profit Margin, Debt to Assets Ratio, Debt to Equity Ratio, and Total Assets Turn Over affect profit growth. Partially Current Ratio, Cash Ratio, Net Profit Margin, Debt to Assets Ratio, Debt to Equity Ratio have no effect on profit growth while Return On Assets and Total Assets Turn Over affect profit growth. Keywords: Current Ratio, Cash Ratio, Return On Assets, Net Profit Margin, Debt to Assets Ratio, Debt to Equity Ratio, total Assets Turn Over, Profit Growth